187k views
4 votes
Factories 24x^2-41x+12

1 Answer

5 votes

Answer:


\displaystyle 24x^(2) - 41x + 12 = 24\left(x - (3)/(8)\right) \cdot \left(x - (4)/(3)\right) = (8x-3)\cdot (3x - 4).

Explanation:

Apply the quadratic formula to find all factors. For a quadratic equation in the form


a\cdot x^(2) + b\cdot x + c = 0,

where
a,
b, and
c are constants, the two roots will be


\displaystyle x_1 = \frac{-b + \sqrt{b^(2) - 4\cdot a \cdot c}}{2a}, and


\displaystyle x_2 = \frac{-b - \sqrt{b^(2) - 4\cdot a \cdot c}}{2a}.

For this quadratic polynomial,


  • a = 24,

  • b = -41, and

  • c = 12.

Apply the quadratic formula to find any
x value or values that will set this polynomial to zero:


\displaystyle x_1 = \frac{-(-41) + \sqrt{(-41)^(2) - 4* 24 * 12}}{2* 24} = (3)/(8).


\displaystyle x_2 = \frac{-(-41) - \sqrt{(-41)^(2) - 4* 24 * 12}}{2* 24} = (4)/(3).

Apply the factor theorem to find the two factors of this polynomial:


  • \displaystyle \left(x - (3)/(8)\right) for the root
    \displaystyle x = (3)/(8), and

  • \displaystyle \left(x - (4)/(3)\right) for the root
    \displaystyle x = (4)/(3).

Keep in mind that simply multiplying the two factors will not reproduce the original polynomial. Doing so assumes that the leading coefficient of
x in the original polynomial is one, which isn't the case for this question.

Multiply the product of the two factors by the leading coefficient of
x in the original polynomial.


\displaystyle 24\left(x - (3)/(8)\right) \cdot \left(x - (4)/(3)\right) = (8x-3)\cdot (3x - 4).

Expand to make sure that the factored form is equivalent to the original polynomial:


(8x-3)\cdot (3x - 4)\\ = (8* 3)x^(2) + ((-3)* 3 + (-4)* 8)\cdot x + ((-3)* (-4))\\ = 24x^(2) - 41x + 12.

User Adam Youngers
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.